Cyberbullying Experienced by University Students - Diana Ioana NICHIFOR; Sorana D. BOLBOACĂ (Applied Medical Informatics)
Background: Cyberbullying2) is defined as “verbally threatening or harassing behavior conducted through such electronic technology as cell phones, e-mail, and text messaging”1. Its perception varies among young individuals across different cultural and environmental contexts, with psychological consequences ranging from anxiety to suicidal ideation3. Our study aimed to analyzed sex differences in the perception and impact of cyberbullying among university students and its relation to psychological well-being. Methods: A cross-sectional study was conducted among Romanian universities students aged 18 or above. Data was collected between October 2024 and November 2024 using an online questionnaire disseminated via social media. Psychological well-being was assessed using the 21-item Depression, Anxiety, and Stress Scale (DASS-21). Results: One hundred and ten students participated (median age: 22 years). Most respondents were women (72, 65%), from urban areas (82, 75%), and unemployed (75, 68%).  Majority of participants (96%) used mobile phones to access social media, with 42% spending over four hours daily online. One-third of respondents were familiar with cyberbullying, with no significant differences between women and men (p=0.4485). Women were more frequently perceived as victims (53.6% women vs. 1.8% men), while men were more often seen as aggressors (51.8% men vs. 0.9% women). However, self-perception as victims was similar between women and men (68.1% women vs. 78.9% men, p=0.4620). Cyberbullying had an impact on emotional state (90.1%), motivation (69.7%), and online interactions (66.7%). Self-assessed depression (p=0.6987) and anxiety (p=0.9883) levels were similar, but stress was statistically significant higher in men (81.6%) than women (62.5%, p=0.0395). Conclusion: Our findings highlight the need for education on cyberbullying and coping strategies to mitigate its impact on emotional state and motivation. Psychological well-being assessments revealed higher stress levels among men in this cohort.